Correlated Relation between Quantum Discord and Entanglement of Two-Atom in Thermal Reservoirs. (10th April 2014) - Yan, Xue-Qun; Yue, Zhuan-Lin
Abstract : We study the time evolution of quantum discord and entanglement of a two-qubit system in thermal reservoirs. We find that there are no simple ordering relations between entanglement and quantum discord for the dynamical evolution behavior; that is, quantum discord may be smaller or larger than entanglement in the evolution process. However, a strong correlation between changes of the ordering relations and the mean photon number is found. In addition, it also shows that entanglement is not the strongest form of nonclassicality.